ROLE OF LECTURERS' INTERPERSONAL SKILLS IN THE COGNITIVE, AFFECTIVE, AND MORAL DOMAINS ON LEARNING OUTCOMES - Hidayati, Permata Ika; Qomariyah, Ismi Nurul; Mistianah, Mistianah; Arifin, As’ad Syamsul (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The learning environment created by the Lecturer has a significant influence on students' academic abilities in addition to being influenced by the students' own innate abilities. This study aims to determine the role of each interpersonal component of the Lecturer and to test the validity of the Lecturer's interpersonal skills ability questionnaire designed by the researcher and on the cognitive, affective, and moral development of Students. This study uses factorial design analysis to see the role of Lecturer's interpersonal skills on Students' cognitive, affective, and moral abilities. 210 Students of Insan Budi Utomo University became Participants who were actively involved in this study. 210 Students came from the 2021 to 2023 intake. Data were collected using a questionnaire to assess Lecturer's interpersonal skills, cognitive, affective, and moral assessment self-report scales of Students. Data analysis used multiple regression and correlation analysis to see the correlation between these variables. The results showed that Students' perceptions of Lecturer's interpersonal skills correlated significantly with learning outcomes in the cognitive, affective, and moral domains of Students. In addition, the questionnaire scale designed by the researcher met the validity criteria because the questionnaire scale could explain what scales were positive and negative predictors of Students' learning outcomes in each domain. This study implies that lecturers must display positive interpersonal skills ability during the learning process or interaction with the class so that the learning process is more effective